Project management leadership building creative teams - Burke, Rory 1952-; Barron, Steve (2014)
"Project Management Leadership is a comprehensive guide to the human factors involved in Project Management, in particular the leadership skills required to ensure successful implementation of current best practice. It provides the latest insights on team building, motivation, collaboration, and networking skills, and the way these can be harnessed to manage a successful project. Exercises and worked examples are provided throughout alongside a fully revised instructor manual"..
Includes bibliographical references and index
Keywords: MATHEMATICS / Applied; Führung; Project management; Leadership; Projektmanagement